Fractal Representation of Composite Elementary Fermions with Positive and Negative Mass Components - Giannini, Judith (European Journal of Applied Sciences, 2024)
The Fractal Rings And Composite Elementary Particles (FRACEP) Model provides an alternate view to the elementary fermion picture. FRACEP represents a dual universe where there are equal amounts of positive and negative matter (mass). Its dual universe construction allows for composite particles of mixed (positive and negative) mass with fractal-based components. The fractal dimension of these composite particles is D = 1.55, and is consistent with other estimates of D for the elementary fermions and other fractal-based composite models. Initial efforts developed an empirically-based two-parameter fit for the mass hierarchy formula, relating the fractal dimension to the composite particle masses. The formula predicts the cross-family (first-generation particles) masses, and the intra-family masses (the three generations within each family). The mass predictions for the structure-based composite particles, as well as, the mass hierarchy are consistent with the Particle Data Group’s 2016/2020-update estimates for the elementary fermions.